TINJAUAN YURIDIS MENGENAI KETERKAITAN ASAS KEBEBASAN BERKONTRAK DENGAN PERJANJIAN BAKU DALAM PERSPEKTIF PERLINDUNGAN KONSUMEN - , ANDI SILVIANA ULFA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study analyzes the relation between the freedom of co ntractâs principle with the presence of standart contract and also study about how to analyzing the presence of standart contract seen by consumer protection aspect. This research is a descriptive analytical research which describes and explains the results of the analysis of the research object systematically. In analyzing subjects, primarly, secondarily and tertierily legal refferences synthetized in normative stages by inventoring refferences and analyzed qualitatively. The results shows that analyzes the relation between the freedom of contractâs pr inciple with the presence of stan dart con tract is standart co ntract itself doesnâ t show the presence of the freedom of co ntract because stan dart co ntract was made unilaterally by creditors with the rules containing many new clausules, additional clausul, continuance and also the alteration that also made unilaterally by creditors while the debitor using the services which are bought and used by the debitors so that thereâre no negotiation to makes the agreement so that the debitors is in bound with the agreement causes by financial pressure. Key Words: freedom of co ntractâs princ iple, standar t con tract, consumer protection